The Distribution and Ecology of Land Snails (Mollusca: Gastropoda) in Limestone Habitats of Western Sarawak - Mohammad Effendi, Marzuki (NIL, 2023)
Species inventories and ecological studies are fundamental tools for assessing the conservation of limestone-associated species such as land snails. Unfortunately, previous inventories of land snail species in the Bau-Serian limestone area lack a systematic checklist with corresponding illustrations for each species. This study aims to investigate the species composition of land snails in the Bau limestone hill clusters in Sarawak, to measure the estimated species richness and sampling effectiveness between live-caught snails and empty snail shells, and finally to investigate the relationships between land snail species and microhabitats. To fill this knowledge gap, systematic and random sampling for land snails were carried out at eight limestone outcrops. All specimens were sorted, identified to species level, and catalogued. Sampling effectiveness between live snails and empty snail shells was determined using cluster-scale completeness ratios for 135 plots. Species completeness analyses were conducted to extrapolate species richness and inventory for different spatial scales. Cluster analyses were conducted to determine the relationship between the species community and assemblages based on the presence, absence, and abundance data of 17 live-caught land snail species. Associations between land snail species and microhabitats sampled were described using the bipartite weighted network. A total of 122 land snail species, of which 18 are new to science, from 58 genera and 24 families, with photographs of each species. The inventory revealed high completeness of sampling for both empty shells and live-taken snails (> 90%) but species diversity is very low for live snails compared to empty snail shells at hill and cluster scales suggesting that some species may have expired locally. Cluster analysis showed that the land snails assemblages do not correspond to different microhabitats, but rather to locality. The limestone area in Bau has a very high degree of endemism due to the low dispersal ability of the land snails. The soil sample appears to have very high species richness, but the species composition contains species from different niches and microhabitats. As the limestone hills in Sarawak are threatened by various habitat degradation activities, further inventories are needed to assess the species richness of land snails in limestone hill clusters to identify and conserve high-priority areas for snail conservation in Sarawak.